IMPLIKASI ASESMEN KOMPETENSI MINIMUM TERHADAP PROSEDUR PEMBELAJARAN LITERASI MEMBACA - Foy Ario; Rahmah Kurniawaty, S.Kom., S.S., M.T. (Jurnal Lingkar Mutu Pendidikan, 2022)
The purpose of this study was to capture the implications of minimum competency assessment (AKM) on the learning procedure of reading literacy for Indonesian teachers at the Indonesian Language MGMP Region 1, East Jakarta. This research is a quantitative research by conducting a survey as a research data collection instrument which is strengthened by interviews at the sample schools. The research data are 15 educational units in which the teacher is a member of the Indonesian Language Subject Teacher Consultation (MGMP) in area 1 East Jakarta at the high school level with 28 respondents. The results showed that teachers had implemented the implications of AKM on the reading procedure 68%. Implications of the AKM for Reading Literacy learning procedures: 1. The teacher knows the results of the 2021 AKM specifically for Indonesian language teachers are the ability of the AKM sample students in each of the schools visited; 2. Indonesian teachers respond to the results of the AKM by planning lessons using reading strategies, and 3. Indonesian teachers introduce reading procedures to teachers of other subjects.